La psicoanalisi come estetica dell’esistenza - Di Bartolo, Michele (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
Michel Foucault, at the beginning of his course on The Hermeneutics of the Subject, excludes and includes, at the same time, psychoanalysis between practices of spirituality. The reason for this double movement is, according to Derrida, in the ambivalence of Freud’s speech. Derridian interpretation of the concept of resistance to analysis offers the possibility of rethinking psychoanalysis as an aesthetics of existence.